Exploring the Efficacy of Mobile Applications in Enhancing English Proficiency of EFL Students: Experimental Studies on Indonesian Senior High School - Ettyani, Ettyani; Aisyah , Siti (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study investigates the effectiveness of mobile applications in improving English competence among Indonesian senior high school students studying English as a Foreign Language (EFL). The study used an experimental approach and involved two groups of students from senior high schools in Indonesia. The experimental group employed certain mobile applications as supplementary tools in their English learning process, whereas the control group received regular classroom instruction without the usage of mobile applications. Data were collected over a three-month period using pre- and post-tests that assessed various areas of English ability, such as vocabulary, grammar, listening, and speaking skills. The results show that students in the experimental group improved their English proficiency significantly more than those in the control group. The usage of mobile applications increased students' interest and motivation while also providing flexible and interactive learning options that older techniques lacked. Qualitative data acquired from student comments and instructor observations support the favorable influence of mobile applications on students' learning outcomes. The study shows that using mobile applications into EFL training can be an extremely effective technique for increasing English proficiency among Indonesian senior high school students. The results suggest that educational stakeholders should consider adding mobile technology into language courses to supplement and improve existing teaching techniques. Future research should concentrate on long-term impacts and investigate the potential of various types of mobile applications in diverse EFL settings.